A fluorogenic probe for core-fucosylated glycan-preferred ENGase. (January 2023) - Ishii, Nozomi; Muto, Hiroshi; Nagata, Mitsuo; Sano, Kanae; Sato, Itsuki; Iino, Kenta; Matsuzaki, Yuji; Katoh, Toshihiko; Yamamoto, Kenji; Matsuo, Ichiro
Abstract: A fluorescence-quenching-based assay system to determine the hydrolytic activity of endo-β- N -acetylglucosaminidases (ENGases), which act on the innermost N -acetylglucosamine (GlcNAc) residue of the chitobiose segment of core-fucosylated N -glycans, was constructed using a dual-labeled fluorescent probe with a hexasaccharide structure. The fluorogenic probe was evaluated using a variety of ENGases, including Endo-M W251N mutant, Endo-F3, and Endo-S, which recognize core fucosylated N -glycans. The occurrence of a hydrolysis reaction was detected by observing an increased fluorescence intensity, ultimately allowing the ENGase activities to be easily and quantitatively evaluated, with the exception of Endo-S. The obtained results clearly indicated the substrate specificities of the examined ENGases. Graphical abstract: Image 1 Highlights: A novel chemical probe, MM3FD, was designed and synthesized. MM3FD can detect the hydrolytic activity of ENGase. ENGase is known to act on core-fucosylated N-glycans. MM3FD enables the high-throughput analysis of the ENGase activity. A microplate reader was employed for carrying out the activity assays.